Reward-Based Crowdfunding Campaigns: Informational Value and Access to Venture Capital - Roma, Paolo; Gal-Or, Esther; Chen, Rachel R. (Information Systems Research, 2018)
We consider an entrepreneur who designs a reward-based crowdfunding campaign when the campaign provides a signal about the future demand for the product and subsequent venture capital is needed. We find that both the informativeness of the campaign and considerations related to gaining access to venture capital funding affect the entrepreneur’s choice of campaign instruments, as well as her decision of whether to run a campaign. In particular, entrepreneurs should launch the campaign either when it is highly informative or when it is not informative at all. For relatively low levels of informativeness, but not so low that the venture capitalist (VC) completely ignores the campaign outcome in his funding decision, our study suggests that the entrepreneur might forgo the opportunity of acquiring information via crowdfunding because the benefits of crowdfunding are insufficient to offset the risk of campaign failure. We also find that the preference of entrepreneurs in favor of crowdfunding is stronger than that of VCs. For backers, we point out that in addition to the risk inherent in new product development, they should be cognizant of the risk that successful campaigns do not guarantee subsequent VC funding. As the use of crowdfunding platforms becomes more prevalent for entrepreneurial projects, our study offers a deeper understanding of the dual role of reward-based crowdfunding in terms of acquiring demand information and raising capital for early-stage start-ups. The online appendix is available at https://doi.org/10.1287/isre.2018.0777 .